Challenging the past in Spain - Elena Martínez Barahona; Mario García Arranz (Oñati Socio-Legal Series)
In recent decades, Spain has enacted two national laws on historical and democratic memory (in 2007 and 2022), alongside numerous laws at the sub-national level. The significance of these laws goes beyond their symbolic value; they not only contribute to collective memory but also acknowledge the plight of victims. This paper aims to analyze the factors influencing regional regulations on historical and democratic memory in Spain. Our focus will be on the drafting processes, exploring the political factors that shape their approval in different regions. Additionally, we will investigate regions that have yet to enact memory laws to understand the reasons behind the absence of such legislation.